Myocardial injury in severe COVID‐19 is similar to pneumonias of other origin: results from a multicentre study. (17th December 2020) - Jirak, Peter; Larbig, Robert; Shomanova, Zornitsa; Fröb, Elisabeth J.; Dankl, Daniel; Torgersen, Christian; Frank, Nino; Mahringer, Magdalena; Butkiene, Dominyka; Haake, Hendrik; Salzer, Helmut J.F.; Tschoellitsch, Thomas; et al.
Abstract: Aims: COVID‐19, a respiratory viral disease causing severe pneumonia, also affects the heart and other organs. Whether its cardiac involvement is a specific feature consisting of myocarditis, or simply due to microvascular injury and systemic inflammation, is yet unclear and presently debated. Because myocardial injury is also common in other kinds of pneumonias, we investigated and compared such occurrence in severe pneumonias due to COVID‐19 and other causes. Methods and results: We analysed data from 156 critically ill patients requiring mechanical ventilation in four European tertiary hospitals, including all n = 76 COVID‐19 patients with severe disease course requiring at least ventilatory support, matched to n = 76 from a retrospective consecutive patient cohort of severe pneumonias of other origin (matched for age, gender, and type of ventilator therapy). When compared to the non‐COVID‐19, mortality (COVID‐19 = 38.2% vs. non‐COVID‐19 = 51.3%, P = 0.142) and impairment of systolic function were not significantly different. Surprisingly, myocardial injury was even more frequent in non‐COVID‐19 (96.4% vs. 78.1% P = 0.004). Although inflammatory activity [C‐reactive protein (CRP) and interleukin‐6] was indifferent, d ‐dimer and thromboembolic incidence (COVID‐19 = 23.7% vs. non‐COVID‐19 = 5.3%, P = 0.002) driven by pulmonary embolism rates (COVID‐19 = 17.1% vs. non‐COVID‐19 = 2.6%, P = 0.005) were higher. Conclusions: Myocardial injury was frequent in severe COVID‐19 requiring mechanical ventilation, but still less frequent than in similarly severe pneumonias of other origin, indicating that cardiac involvement may not be a specific feature of COVID‐19. While mortality was also similar, COVID‐19 is characterized with increased thrombogenicity and high pulmonary embolism rates.